'I wouldn't have been culturally safe': health science students' experiences of transformative learning within Indigenous Studies. Issue 4 (7th June 2019) - Bullen, Jonathan; Roberts, Lynne
ABSTRACT: Despite a significant body of literature espousing the transformative impacts of Australian Indigenous Studies curriculum upon students, there remains a limited body of work related to how these students experience and learn within this complex environment. This is particularly notable for research aligned with Mezirow's transformative learning theory. Reporting on a qualitative study, this paper offers a perspective into students' transformative experiences within a tertiary first-year Indigenous Studies health course. Thirteen non-Indigenous students were interviewed about their learning experiences within this context. Explicitly framed by Mezirow's transformative learning theory, thematic analysis findings suggest students consistently experience precursor steps to transformative learning including disorienting dilemmas, self-examination with guilt or shame, critical reflection on assumptions, exploration of new roles, and trying on new roles. The manifestation of these steps highlights the ways in which students experience learning in this space, and a range of elements influencing this – from students' own positioning and approaches to learning, to the nature of the curricular and pedagogical approaches. This study offers nuanced insight into the complexity of students' transformative learning experiences, suggesting students hold a range of contradictory perspectives at any one time. If curricular models are to be effective for the broader student body, we propose that (1) the complex intersection of students' identity development, need for group belonging, learning approach, limitations in existing knowledge and capacity for complex thought requires further consideration in this context, and (2) greater institutional investment is necessary in both the development of educators in this space, and educational opportunities beyond first-year, lest we risk reinforcing extant beliefs and paradigms held by non-Indigenous Australians about Indigenous Australians, and a continuation of the health disparities these curricular offerings are designed to alleviate.